2019
DOI: 10.12659/msm.914435
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Cognitive Decline After Cardiac Surgery: A Narrative Review of Current Knowledge in 2019

Abstract: The growing number of publications concerning postoperative cognitive decline (POCD) after cardiac surgery is indicative of the health-related and economic-related importance of this intriguing issue. Significantly, the reported POCD incidence over the years has remained steady due to various unresolved challenges regarding the examination of this multidisciplinary topic. In particular, a universally accepted POCD definition has not been established, and the pathogenesis is still vaguely understood. However, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 89 publications
(173 reference statements)
1
114
0
7
Order By: Relevance
“…Moreover, brain impairment after heart surgery was found to be more extensive and not confined to hippocampal brain regions in the animal study [12]. A review by Glumac et al summarized that the current definition of PND is controversial and lacks consistency and the inflammatory response after cardiac surgery plays an important role in the pathogenesis of PND [13]. Which is worthy of further study.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, brain impairment after heart surgery was found to be more extensive and not confined to hippocampal brain regions in the animal study [12]. A review by Glumac et al summarized that the current definition of PND is controversial and lacks consistency and the inflammatory response after cardiac surgery plays an important role in the pathogenesis of PND [13]. Which is worthy of further study.…”
Section: Discussionmentioning
confidence: 95%
“…Spatial reference memory in mice from the control and the multiple anesthesia/surgery groups was evaluated in the Morris water maze (MWM) since the second day after the last surgery. In different cohorts of animals, 8 mice from control, single anesthesia/surgery, and multiple anesthesia/surgery groups were euthanized at each time point (6,24, and 48 h after surgery) in each group. Hippocampus tissue and serum were harvested for the measurements of IL-1β, IL-6, TNF-α, and IL-10 by enzyme-linked immunosorbent assay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
“…The condition is characterized by impaired learning and memory and may persist for months and years after surgery [4,5]. POCD is thought to be associated with major surgery and advanced age [6,7], and there is no doubt that older individuals are more likely to develop POCD [8]. Although POCD does occur in adults in clinical settings, whether adult mice develop similar learning and memory impairment after anesthesia/surgery remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, tests are not free of interfering confounders, such as ceiling or floor (basement) effect. Glumac et al found over 100 different neuropsychological tests that were being used for the diagnosis of delirium [ 59 ]. Difficulties and problematic use of them result indirectly from the non-uniform use of the definition of POD and postoperative cognitive dysfunction (POCD) [ 19 , 58 ].…”
Section: Diagnosing Delirium After Cardiac Surgerymentioning
confidence: 99%
“…Due to the multitude of diagnostic tests, many studies cannot be compared, and the results obtained in many different ways may mask the real number of patients with delirium [ 19 ]. Sheth et al proposed a period of seven days from the time of cardiac surgery until the test for cognitive impairment due to the direct influence of drugs and the hospital environment on the patient’s condition, while Glumac et al stated that the tests should be performed preoperatively and in the early postoperative period (seven to 14 days after the procedure), but also even 6 to 9 months after surgery [ 59 , 60 ].…”
Section: Diagnosing Delirium After Cardiac Surgerymentioning
confidence: 99%